ANALISIS PENGENDALIAN DEFECT DEFORMASI PADA BRACKET SENSOR BLIND SPOT MONITORING (BSM) DENGAN METODE FMEA DAN SIKLUS PDCA DI PT XYZ - Tahrim; Mukhlisin; Rudy Effendy Listyanto (Jurnal Teknik Industri Universitas Dirgantara Marsekal Suryadarma (Unsurya), 2026)
PT XYZ is one of the automobile assembly manufacturers in Indonesia that bears a significant responsibility to ensure every vehicle produced complies with international quality standards. One of the major challenges in the assembly process is the occurrence of deformation-type defects on the Blind Spot Monitoring (BSM) sensor bracket. This deformation may aris due to various factors, such as improper installation processes or inappropriate component handling conditions along the production line. If not properly controlled, deformation of the bracket not only degrades the functionality of the BSM sensor but also leads to increased repair costs, production delays, and potential product recalls, which could result in substantial financial losses for the company. Based on trace-back defect analysis, the defect was identified to originate in the body production and inspection departments, specifically at the right-hand (RH) side member line. Furthermore, the Failure Mode and Effects Analysis (FMEA) indicated that the factors with the highest Risk Priority Number (RPN), and therefore the main improvement priorities, were related to man (human factors) and method (process-related factors). Following the implementation of improvement actions, the deformation defect was successfully reduced and completely eliminated, achieving a 100% defect reduction, from 0.0024 defects per unit (d/u) to 0 d/u throughout the observation period.